2022
DOI: 10.1186/s13578-022-00836-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into non-alcoholic fatty liver disease and dementia: insulin resistance, hyperammonemia, gut dysbiosis, vascular impairment, and inflammation

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a metabolic disease characterized by multiple pathologies. The progression of dementia with NAFLD may be affected by various risk factors, including brain insulin resistance, cerebrovascular dysfunction, gut dysbiosis, and neuroinflammation. Many recent studies have focused on the increasing prevalence of dementia in patients with NAFLD. Dementia is characterized by cognitive and memory deficits and has diverse subtypes, including vascular dementia, Alzheimer’s deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 203 publications
(300 reference statements)
0
25
0
Order By: Relevance
“…Researches have shown that embedding catgut in specific parts of the skin (acupoint catgut embedding therapy) can continuously generate benign stimulation, affect neurotransmitters and local circulation, repair damaged neural loop networks, restore normal central function, regulate immunity, and inhibit the release of inflammatory factors (5)(6)(7). Besides, our early works and others have demonstrated that inflammation plays an important role in the development of VD (8)(9)(10)(11). Tolllike receptor 4 (TLR4) is a kind of toll-like receptor (TLR), which is an important pattern recognition receptor expressed in innate immune cells.…”
Section: Original Articlementioning
confidence: 99%
“…Researches have shown that embedding catgut in specific parts of the skin (acupoint catgut embedding therapy) can continuously generate benign stimulation, affect neurotransmitters and local circulation, repair damaged neural loop networks, restore normal central function, regulate immunity, and inhibit the release of inflammatory factors (5)(6)(7). Besides, our early works and others have demonstrated that inflammation plays an important role in the development of VD (8)(9)(10)(11). Tolllike receptor 4 (TLR4) is a kind of toll-like receptor (TLR), which is an important pattern recognition receptor expressed in innate immune cells.…”
Section: Original Articlementioning
confidence: 99%
“…The pool of available data points toward the strong linkage between the development and onset of AD and liver dysfunction and the consequent systemic metabolism pathologies [ 161 , 162 ]. Nho et al [ 163 ] have correlated aberrant liver function (represented by the activities of serum-based liver enzymes alanine aminotransferase (ALT) and aspartate aminotransferase (AST)) in 1,500 AD patients to more significant brain atrophy detected by MRI, disrupted brain glucose metabolism measured by 18 F-FDG PET, and increased Aβ accumulation showed by 18 F-florbetapir PET.…”
Section: Ad As Insulinopathymentioning
confidence: 99%
“…Furthermore, the relationship between NAFLD/NASH and mood disorders may be bi-directional in nature as metabolic liver disease has been reported to be an independent risk factor for emerging anxiety and depression ( Labenz et al, 2020 ). Finally, NAFLD/NASH has been implicated in cognitive decline associated with dementia ( Cheon and Song, 2022 ; Hadjihambi, 2022 ; Mikkelsen et al, 2022 ), highlighting complex and yet to be clearly defined relationships among the regulation of mood/cognition, whole-body energy metabolism, and liver disease. Factors including genetic susceptibility, socioeconomic factors, insulin resistance, systemic inflammation and psychiatric medications each contribute to increased prevalence of NAFLD in psychiatric populations.…”
Section: Prevalence Of Non-alcoholic Fatty Liver Disease/non-alcoholi...mentioning
confidence: 99%